Bold factors influencing Indonesian processed cocoa export to major importing countries; Do export promotion agencies matter? - Sari, Ratna Mega; Novianti, Tanti; Agbolosoo, John Atsu (Anjoro: International Journal of Agriculture and Business, 2025)
The role of ITPC (Indonesia Trade Promotion Center) as an export promotion agency has begun to be questioned due to the fluctuation in Indonesia's non-oil and gas export value. Some of the ITPCs are in major importing countries of Indonesian cocoa. This study aims to analyze the factors influencing Indonesian processed cocoa exports (HS1803/cocoa paste) to major importing countries, with a focus on the effect of ITPC, Indonesia's export promotion agency, in foreign countries. The types of data used are secondary data from 2005 to 2022, which involve the top seven importing countries: Malaysia, China, India, the United States, Brazil, Germany, and the Philippines. The data were analyzed using the gravity model. The data were obtained from various sources, including Statistics Indonesia, the World Bank, WITS, the Ministry of Industry, and other relevant institutions. Data processing was conducted by using panel data regression with EViews 10. Real exchange rate and the Indonesian Trade Promotion Center (ITPC) had a positive and significant impact on Indonesia's processed cocoa exports The ITPC dummy variable in the estimation of the model has a coefficient of 1.047, which means that if there is an ITPC in the destination importing country, the export value of Indonesian cocoa will be higher by as much as 104.7 percent compared to the importing destination country without ITPC Generally, the result of this research can be a recommendation to continue the existence of ITPC. The presence of ITPC will establish market intelligence and facilitate the export of processed cocoa to importing countries.